In Silico Discovery and Evaluation of Inhibitors of the SARS-CoV-2 Spike Protein–HSPA8 Complex Towards Developing COVID-19 Therapeutic Drugs - Liberty T. Navhaya; Thabe M. Matsebatlela; Mokgerwa Z. Monama; Xolani H. Makhoba (Viruses)
The SARS-CoV-2 spike protein is pivotal in the COVID-19 virus’s life cycle, facilitating viral attachment to host cells. It is believed that targeting this viral protein could be key to developing effective COVID-19 prophylactics. Using in silico techniques, this study sought to virtually screen for compounds from the literature that strongly bind and disrupt the stability of the HSPA8–spike protein complex. To evaluate the interactions between the individual proteins and the protein complex attained from protein–protein docking using BioLuminate, molecular docking was performed using the Maestro Schrodinger Suite. The screened small molecules met all bioavailability conditions, Lipinski’s and Veber’s rules, and the required medicinal chemistry properties. Protein–protein docking of the spike protein and HSPA8 identified the optimal pose with a PIPER cluster size of 65, a PIPER pose energy of −748.301 kcal/mol, and a PIPER pose score of −101.189 kcal/mol. Two small molecules, NSC36398 and NSC281245, showed promising docking scores against the spike protein individually and in a complex with HSPA8. NSC36398 had a docking score of −7.934 kcal/mol and a binding free energy of −39.52 kcal/mol with the viral spike protein and a docking score of −8.029 kcal/mol and binding free energy of −38.61 with the viral protein in complex with HSPA8, respectively. Mevastatin had a docking score of −5.099 kcal/mol and a binding free energy of −44.49 kcal/mol with the viral protein and a docking score of −5.285 kcal/mol and binding free energy of −36.65 kcal/mol with the viral protein in complex with HSPA8, respectively. These results, supported by extensive 2D interaction diagrams, suggest that NSC36398 and NSC281245 are potential drug candidates targeting SARS-CoV-2 spike protein.